Letramentos Acadêmicos e o processo de representação do graduandos em Letras na contemporaneidade - Frota, Joyce Almagro Squinello [UNESP] (2014)
The general aim of this paper is to study written textual productions produced by university students, enrolled in a Portuguese and Literature Language course at a public university, with regard to social representations (MOSCOVICI, 2001; 2011) that these students project from their role as future teachers and university students who will work in a context characterized by (new) reading practices and writing. The starting hypothesis is that there is a conflict between the institution expectations with regard to textual written production and what the university students produce effectively. In a particularized way, it interests: (i) the studying of linguistic-discursive marks that point to these representations; (ii) the studying of which interlocutors the graduating students dialogue to in textual productions; (iii) the studying of the supporting material for the submitted proposal of written production by the institution to the university students. The theoretical and methodological assumptions are derived from the New Literacy Studies and Studies of Writing and Discourse. The set of the material is made up of 53 textual productions written by students of that course, in 2012, published in a closed group from an internet social networking. As main results there are the conflicts from the perspective of the university students: (i) between what the academic institution offers and what he would need in the classroom; (ii) between having a job and being devalued professionally; (iii) between who has or has not updated the field of technology. It is evidenced also by the absence, the dialogue that the university students establish with the academic- scientific discourse, distancing themselves from the institution